Bibliometric Analysis and Literature Review on Organizational Barries in the Audit Proses - Surya Sobirin Singarimbun; Izzati Salsabila; Nayla Tushifa; Aulia Irsalina Saragih; Hasan Sazali (PERSPEKTIF: Journal of Social and Library Science, 2026)
Organizational barriers in the audit process remain a significant concern because they directly influence supervisory effectiveness, decision-making quality, and the achievement of organizational objectives. Challenges such as inadequate coordination, limited human resources, insufficient auditor competence, and ineffective communication frequently hinder the successful implementation of audit activities. This study aims to examine the development of research on organizational barriers in the audit process through bibliometric mapping and literature review to identify research trends, thematic relationships, and future research opportunities. The study employs a quantitative approach using bibliometric analysis integrated with a literature review. Data were collected from scientific publications published between 2016 and 2026 through Google Scholar and Semantic Scholar using the Publish or Perish application. The collected data were subsequently analyzed using VOSviewer through network, overlay, and density visualizations. The findings reveal that the themes of communication and barrier constitute the most dominant and interconnected topics within the field of organizational audit studies. Research trends indicate a gradual shift from administrative and procedural perspectives toward strategic communication, information quality, technological integration, and stakeholder involvement. Density analysis further demonstrates that topics related to digital transformation, communication technologies, audit strategies, and collaborative governance remain underexplored. These findings suggest that audit effectiveness is determined not only by control and compliance mechanisms but also by the quality of organizational communication and the ability to manage emerging barriers. The study concludes that strengthening communication systems, integrating technological innovations, and enhancing stakeholder coordination are essential for developing a more adaptive, collaborative, and sustainable audit process in contemporary organizational environments.